Ethnoveterinary plants of Pakistan: a review - Muhammad Abdul Aziz; Amir Hasan Khan; Andrea Pieroni (BMC, 2020)
Abstract Background Ethnoveterinary medicine is crucial in many rural areas of the world since people living in remote and marginal areas rely significantly on traditional herbal therapies to treat their domestic animals. In Pakistan, communities residing in remote areas, and especially those still attached to pastoralist traditions, have considerable ethnoveterinary herbal knowledge and they sometimes use this knowledge for treating their animals. The main aim of the study was to review the literature about ethnoveterinary herbals being used in Pakistan in order to articulate potential applications in modern veterinary medicine. Moreover, the review aimed to analyze possible cross-cultural and cross regional differences. Methods We considered the ethnobotanical data of Pakistan published in different scientific journals from 2004 to 2018. A total of 35 studies were found on ethnoveterinary herbal medicines in the country. Due to the low number of field studies, we considered all peer-reviewed articles on ethnoveterinary herbal practices in the current review. All the ethnobotanical information included in these studies derived from interviews which were conducted with shepherds/animals breeders as well as healers. Results Data from the reviewed studies showed that 474 plant species corresponding to 2386 remedies have been used for treating domestic animals in Pakistan. The majority of these plants belong to Poaceae (41 species) followed by the Asteraceae (32 species) and Fabaceae (29 species) botanical families, thus indicating a possible prevalence of horticultural-driven gathering patterns. Digestive problems were the most commonly treated diseases (25%; 606 remedies used), revealing the preference that locals have for treating mainly minor animal ailments with herbs. The least known veterinary plants recorded in Pakistan were Abutilon theophrasti, Agrostis gigantea, Allardia tomentosa, Aristida adscensionis, Bothriochloa bladhii, Buddleja asiatica, Cocculus hirsutus, Cochlospermum religiosum, Cynanchum viminale, Dactylis glomerata, Debregeasia saeneb, Dichanthium annulatum, Dracocephalum nuristanicum, Flueggea leucopyrus, Launaea nudicaulis, Litsea monopetala, Sibbaldianthe bifurca, Spiraea altaica, and Thalictrum foetidum. More importantly, cross-cultural comparative analysis of Pathan and non-Pathan ethnic communities showed that 28% of the veterinary plants were mentioned by both communities. Cross-regional comparison demonstrated that only 10% of the plant species were used in both mountain and plain areas. Reviewed data confirm therefore that both ecological and cultural factors play a crucial role in shaping traditional plant uses. Conclusion The herbal ethnoveterinary heritage of Pakistan is remarkable, possibly because of the pastoral origins of most of its peoples. The integration of the analyzed complex bio-cultural heritage into daily veterinary practices should be urgently fostered by governmental and non-governmental institutions dealing with rural development policies in order to promote the use of local biodiversity for improving animal well-being and possibly the quality of animal food products as well.